Developing Career Capital for Global Careers: The Role of International Assignments - Dickmann, Michael; Harris, Hilary (Elsevier, 2005)
Creating organizational processes which nurture global careers is a key task for global companies. International assignments are normally viewed as positive by both individuals and organizations for the development of global career competencies. This paper reports a qualitative study into the effects of international assignments on global careers. The research takes account of the dual dependency within global careers by contrasting individual and organizational perspectives. It highlights the importance of informal norms and develops a more nuanced picture of the impact of an international assignment on the career capital of individuals within one global organization.